Channel-mediated high-affinity K+ uptake into guard cells from Arabidopsis. - Brüggemann, Lioubov; Dietrich, Petra; Becker, Dirk; Dreyer, Ingo; Palme, Klaus; Hedrich, Rainer (Proceedings of the National Academy of Sciences of the United States of America, 1999)
Potassium uptake by higher plants is the result of high- or low-affinity transport accomplished by different sets of transporters. Although K+ channels were thought to mediate low-affinity uptake only, the molecular mechanism of the high-affinity, proton-dependent K+ uptake system is still scant. Taking advantage of the high-current resolution of the patch-clamp technique when applied to the small Arabidopsis thaliana guard cells densely packed with voltage-dependent K+ channels, we could directly record channels working in the concentration range of high-affinity K+ uptake systems. Here we show that the K+ channel KAT1 expressed in Arabidopsis guard cells and yeast is capable of mediating potassium uptake from media containing as little as 10 microM of external K+. Upon reduction of the external K+ content to the micromolar level the voltage dependence of the channel remained unaffected, indicating that this channel type represents a voltage sensor rather than a K+-sensing valve. This behavior results in K+ release through K+ uptake channels whenever the Nernst potential is negative to the activation threshold of the channel. In contrast to the H+-coupled K+ symport shown to account for high-affinity K+ uptake in roots, pH-dependent K+ uptake into guard cells is a result of a shift in the voltage dependence of the K+ channel. We conclude that plant K+ channels activated by acid pH may play an essential role in K+ uptake even from dilute solutions.